In the wake of Terra Nullius? - C Perrin; B. Ripperger (Law Text Culture, 1998)
Terra nullius is the principle of a violence that inheres in every origin. And, in its wake, there is no law, no text, no culture, free ofthat violence. The origin is no accident. Terra nullius is not an historical error. Our conceptual legacy is the unsettled and unsettling history of this violence. It demands critical... thinking. Or else... we are condemned to repeat this origin again and again.